KEKERASAN PADA ANAK DALAM SUDUT PANDANG HUKUM ISLAM - Nadya 'Afriati Mumtaz; Hisny Fajrussalam; Lena Putri Tejakusuma; Liana Lestari (Peneliti.net, 2023)
This study aims to find out how the Islamic perspective on violence against children. This type of research is literature study research, namely the author obtains and collects related data through books, articles, and journals that are relevant to the research themes discussed. The subject of this research is related to violence against children. Child violence is one of the important problems in the view of Islamic law. Islamic law places great emphasis on protecting children from all forms of violence and neglect, as well as guaranteeing their rights to receive good care and education. While the object of research is the Islamic point of view. Islam has always been closely related to every aspect of human life. In overcoming the problems that occur, Islam always adheres to the Al-Qur'an and hadith as a guide. There are no exceptions regarding the protection and education of children which are found in the Al-Quran. Islamic law guarantees children's rights in matters of inheritance, guardianship and legal protection. In addition, Islamic law forbids all forms of violence against children, both physical and psychological, as well as neglect that can endanger their safety and well-being. Parents who commit acts of violence or neglect of children may be subject to legal sanctions in accordance with applicable legal provisions. In conclusion, Islamic law pays great attention to protecting children and guaranteeing their rights. Child protection must be carried out responsibly by parents, families